Factors related to depression among transgender male to female (mtf) in Kuantan, Pahang : a qualitative study - Md Hadis, Nur Diyana; Draman, Samsul; Samsudin, Suhaiza; Md Rosli, Ahmad Nabil; Ab Rahman, Norny Syafinaz; Yusof, Muhammad Zubir (2020)
Introduction: Transgender male to female is a marginal group of people and their health is a neglected issue, and transgender people are underserved and stigmatized. They are particularly vulnerable to mental health concerns and psychological distress. There are multiple associated factors related to depression. This study aims to assess the associated factors related to depression among transgender male to female in Kuantan, Pahang. Material and methods: This is a qualitative study conducted among 24 informant among transgender male to female in Kuantan, Pahang. It involved 4 focus group discussion which consist of 5-7 informant during each interview. Interview was conducted using semi structured interview. Purposive sampling was done to ensure diversity of informant. Data was transcribed verbatism and analysed using content analysis. Results: All informant were Malay and Muslim with age ranging from 22-65 years old. There are 6 themes emerges as factor associated to depression are (i) family acceptance and support ;disowned, unknown family ties, family acceptance, (ii) discrimination and prejudice ;co worker, unemployment, disgusting reaction from society, improper reaction government sector staff, (iii) health status, HIV infection, (iv) reduce self worth, market drop as getting older, self-achievement, discrimination, (v) challenges to change , abstinence, condemnation by colleague, and (vi) substance use , poor coping. Conclusion : Majority of informant expressed discrimination as the common factors associated with depression and they are being discriminated in so many ways. Thus, it is important to educate our health care provider to be non-judgemental towards them and provided service friendly clinic in order to engage them in our treatment and services.